Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/cam4.1547
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA LINC00152 promotes cell proliferation through competitively binding endogenous miR‐125b with MCL‐1 by regulating mitochondrial apoptosis pathways in ovarian cancer

Abstract: Recently, an increasing number of studies have focused on the key function of long noncoding RNAs (lncRNAs) in biological activity. Abnormal lncRNA expression was found to relate to the development and pathogenesis of multiple cancers. LncRNA LINC00152 served as an oncogene in multiple cancers; however, its role in ovarian cancer remains unknown. In our research study, LINC00152 was upregulated in ovarian cancer tissues and cell lines. An increasing LINC00152 level was positively correlated with the histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 36 publications
2
50
0
Order By: Relevance
“…18,19 However, little study has investigated the regulatory effect of mRNA on lncRNA through sponging miRNA. 18,19 However, little study has investigated the regulatory effect of mRNA on lncRNA through sponging miRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 However, little study has investigated the regulatory effect of mRNA on lncRNA through sponging miRNA. 18,19 However, little study has investigated the regulatory effect of mRNA on lncRNA through sponging miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…However, growing evidence suggests that lncRNAs and miRNAs play crucial roles in various biological processes but their expression dysregulation is also implicated in regulating or coordinating diverse pathologies (eg, cancer). 18,19 However, the ceRNA hypothesis also provide a possibility that other RNA transcripts may conversely influence the expression or function of lncRNAs through competitively combining with miRNA. [7][8][9][10][11][12] As increased lncRNA-UCA1 is associated with poor overall survival and disease-free survival of GC patients, lncRNA-UCA1 has been suggested as a promising biomarker for the early detection and prognosis prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, it was also identified that LINC00152 knockdown alone had no significant effect on apoptosis and the expression of drug resistance-associated genes (MDR1, MRP1 and GSTπ) in COC1 cells. Contrastingly, the data from the study by Chen et al (12) demonstrated that LINC00152 silencing significantly promoted apoptosis in the ovarian cancer SKOV3 and A2780 cell lines. This result is inconsistent with ours, potentially due to the selection of different cell lines.…”
Section: Discussionmentioning
confidence: 78%
“…Another previous study suggested that LINC00152 confers oxaliplatin resistance by regulating the expression of miR-193a-3p, and that it may be an independent prognostic factor for colon cancer (26). Notably, a recent study by Chen et al (12) demonstrated that LINC00152 was upregulated in ovarian cancer tissues and cell lines, and that LINC00152 knockdown promoted apoptosis and inhibited tumor growth, suggesting a pro-cancer effect of LINC00152. To the best of our knowledge, in the present study, the sensitization effect of LINC00152 on cisplatin was evaluated for the first time in ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation